2017
DOI: 10.1007/s11224-017-0934-y
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation for the reaction of N2O with CO catalyzed by Pt-Graphene

Abstract: To find an efficient catalyst to catalytic conversion of hazardous gases maybe the important way for solving environmental problems. We performed the first-principles density functional theory (DFT) to investigate the CO oxidation by using N 2 O as an oxidizing agent over an Pt-Graphene catalyst. The results indicated that CO oxidation by N 2 O on Pt-Graphene may occur via two pathways: (1) Adsorption of N 2 O followed by CO and (2) Adsorption of CO followed by N 2 O. Although the CO was more likely to adsorb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The above results demonstrated that the adsorption energy of N 2 O is higher than that of CO, and N 2 O is preferentially adsorbed on V/C 2 N and Mn/C 2 N surfaces. By comparison with previous catalysts, we found that the adsorption of CO on the Pt‐doped graphene [ 26 ] is stronger than that of N 2 O, meaning that the V/C 2 N and Mn/C 2 N catalysts in this paper may have higher selectivity (Table 2).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The above results demonstrated that the adsorption energy of N 2 O is higher than that of CO, and N 2 O is preferentially adsorbed on V/C 2 N and Mn/C 2 N surfaces. By comparison with previous catalysts, we found that the adsorption of CO on the Pt‐doped graphene [ 26 ] is stronger than that of N 2 O, meaning that the V/C 2 N and Mn/C 2 N catalysts in this paper may have higher selectivity (Table 2).…”
Section: Resultsmentioning
confidence: 71%
“…From Figure 5d,f there are powerful interaction areas between the adsorbed TM and O atoms, indicating that the electrons on the 3 d orbitals of the TM atom transfer to the π * orbitals of the adsorbed N 2 O, thereby promoting the decomposition of N 2 O molecule. Furthermore, as shown in Table 2, V/C 2 N and Mn/C 2 N show remarkable adsorption performance compared with the adsorption energies (−4.9 and −21.1 kcal mol −1 ) and electron transfer values (0.01 and −0.66 e) of N 2 O on Pt‐doped graphene [ 26 ] and Ge‐doped graphene. [ 71 ] For N 2 O adsorption, N‐end was also examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst an increasing number of single-atoms, most have been focusing on supporting noble metal atoms like Pt or Pd on metal oxide or metal surfaces [14,15]. Dopants such as P [16], Si [17,18], Fe [19,20], Pt [21,22], Pd [23,24], Ni [25,26] substitute with carbon atoms in the graphene sheet and can significantly enhance the properties of graphene sheet. On the other hands, tailoring the graphene sheet by introducing defects [27,28] or heteroatoms (e.g., N, B, P) [29] into the structure of graphene sheet will speed up the catalytic reactions occurred on the surface [30,31] and modulate the electronic properties of the catalyst [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Due to its large specific area, high electron mobility (>200,000 cm 2 ∙V −1 ∙s −1 ), high thermal conductivity (>4000 W∙m∙K −1 ) and good tensile strength, graphene has been widely used in the experimental and theoretical studies of the catalyst matrix. Many scholars have studied the catalytic decomposition of N 2 O on the surfaces of modified graphene in the last decades, and they discovered that adding Fe [24], Ga [25], Al [25,26], Se [27], Si [27,28,29], Pt [30] and ZnO [31] to modify graphene’s properties can be helpful to develop its catalytic effect upon the decomposition of N 2 O. Graphene oxide (GO) is a kind of graphene derivative, containing an oxygen functional group, which can be prepared by Hummers’ Method, and regarded as a substitute for graphene nanomaterials at low cost [32]. Lv et al [33] have explored the adsorbing and decomposing process of our N 2 O molecule on the surfaces of Al-decorated graphene oxide (Al–GO), and they reported that the physically-adsorbed N 2 O could be decomposed to the N 2 molecule and an O atom bonded on Al–GO exothermally (2.33 eV per N 2 O molecule), the energy barrier of which is 0.5 eV.…”
Section: Introductionmentioning
confidence: 99%